Real-Time Changes in the Comfort of a Toric, Monthly, Soft Contact Lens Over a Long Day of Wear - Lievens C; Perkins A; Rayborn E; Wang Y; Franklin Q; May K; Kannarr S; Bromley M; Pucker AD (Clinical Optometry)
Chris Lievens,1,2 Amy Perkins,1 Elyse Rayborn,1 Yueren Wang,1 Quentin Franklin,3 Kristopher May,2,4 Shane Kannarr,2,5 Morgan Bromley,1 Andrew D Pucker6 1Southern College of Optometry, Memphis, TN, USA; 2Eye Research Associates, Pittsburg, KS, USA; 3University of Alabama at Birmingham, School of Optometry, Birmingham, AL, USA; 4Coldwater Vision Center, Coldwater, MS, USA; 5Kannarr Eye Care, Pittsburg, KS, USA; 6Eminent Ophthalmic Services, LLC, Milledgeville, GA, USACorrespondence: Chris Lievens, Southern College of Optometry, Memphis, TN, 38104, USA, Email clievens@sco.eduPurpose: The purpose of this work was to determine the comfort performance of a toric, monthly, silicon hydrogel CL (lehfilcon A; TOTAL30 for Astigmatism) over a long day of wear.Methods: This was a 1-month, 3-visit, prospective, single-arm study. Adult, 18- to 45-year-old CL wearers with good vision who were minimally symptomatic (CLDEQ-8 scores ≤ 12) were enrolled. Subjects were required to have astigmatism ranging from − 0.75 D to − 2.50 D in each eye and were required to wear the study CLs from about 8:00 AM until 12:00 AM each day. Comfort data with the study CL throughout the wear day were collected via text messaging.Results: A total of 47 subjects who had a mean ± SD age of 29.5 ± 7.0 years were analyzed. Within a specified time point across the month of wear, CL comfort did not vary (all p-value ≥ 0.82), yet CL comfort did decrease across the wear day for all days evaluated (all p-value < 0.001). Most subjects found their CLs to be comfortable with only 1.8% of subjects reporting an uncomfortable score at CL application and only 8.5% of subjects reporting an uncomfortable score after 16 hours of CL wear.Conclusion: A high level of consistency and predictability in comfort was found within the first month of wearing lehfilcon A CLs. This suggests that patients with minimal CL-related discomfort at initial fitting of a lehfilcon A CL may likely tolerate longer wear time with minimal discomfort across the entire month of wear.Clinical Trials.gov Id: NCT06052046.Keywords: comfort, contact Lenses, lehfilcon A, toric, visual analog scale